Extracellular pressure stimulates adhesion of sarcoma cells via activation of FAK and Akt - Perry, Brandon C. (2010)
SUMMARY: Pressure increases sarcoma cell adhesiveness via intracellular activation of Akt and FAK. Perioperative manipulation or forces in lymphatic or circulatory systems may potentiate local recurrence or distant metastasis. BACKGROUND: The effect of extracellular pressure on adhesion and adhesiogenic focal adhesion kinase (FAK) and Akt signaling in sarcomas was investigated. METHODS: Human sarcoma cells (HT-1080 fibrosarcoma, KHOS-240S osteosarcoma, A-673 rhabdomyosarcoma) were subjected to increased pressure followed by adhesion assay. Two cell lines were pretreated with the FAK inhibitor 1,2,4,5-benzenetetraamine tetrahydrochloride (Y15) or Akt IV inhibitor, followed by Western analysis for activated FAK and Akt. Parallel studies were conducted in cells from a resected human fibrous histiosarcoma. RESULTS: Pressure increased adhesion in all three sarcoma lines and primary histosarcoma cells by 7–18% (n=6, p<0.01 each). Pressure activated FAK and Akt (n=5, p<0.01). Inhibiting FAK or Akt inhibited FAK or Akt phosphorylation and the stimulation of adhesion by increased pressure (n=5 each, p<0.01 each). CONCLUSION: Pressure increases sarcoma cell adhesiveness via Akt and FAK. Perioperative manipulation or forces in lymphatic or circulatory systems may potentiate local recurrence or distant metastasis.